Autism Spectrum Disorder (ASD): A brief report on its main characteristics - Araújo , Flavia Aparecida Freire (Seven Editora, 2023)
The present study, of bibliographic origin, sought to identify in the literature some main characteristics and historical discussions about autism and also to describe what has appeared as more comprehensive characteristics in children with autism. Autism Spectrum Disorder (ASD) is a developmental disorder, persistent throughout life, as it has no cure, nor consistently clarified causes, however, it is important that teachers, family members, parents and other professionals have some basic information about the characteristics of autism so that they can seek their rights regarding the teaching and learning process. DOI:https://doi.org/10.56238/interdiinovationscrese-019